PENGARUH SUMBER KARBON TERHADAP PRODUKSI ENZIM INULINFRUKTOTRANSFERASE DARI Nonomuraea sp - Yetti Mulyati I; Sri Pudjiraharti; Een Sri Endah; Tanaka tanaka; Teruo Sone; Asano K (Research Center for Chemistry - LIPI, 2011)
The aims of this research is to produce inulinfructotransferase enzyme with potentially benefit of bacteria Actinomycetes which was isolated from Indonesia soils to produce Difructoanhydride-Ill (DFA III), a compound has physiology activities to enhance calsium absorption of rats. cows and human colons so that the materials can be applied as antiosteoporosis. The processing of inulinfructotransferase enzyme from Nonomuraea sp by usingshakeflask level and study the influence of carbohydrate source were conducted. This enzyme has optimum temperature at 65rtC,higher than optimum temperature which has found before and the activities was stable at 70dc for 20 minutes. So that the enzyme has potentially applicable for industry scale. The results indicated that optimation condition for processing inulinfructotransferase enzyme of Nonomuraea sp : temperature sore. incubation time 48 hours.carbon source of inulin 20 g/L, nitrogen source 5g/L, noyeast extract added, the enzyme activities was 7,3 Unit/ml; However,when medium contains yeast extract 0,2 gIL,the inulinfructotransferase enzyme activity was 14,6 Unit/mL.Keywords: Inulinfructotransferase enzyme, Nonomuraeasp.inulin. yeast extract, DFAII